Osteonecrosis of the Jaw in Myeloma Patients Receiving Denosumab or Zoledronic Acid. Comment on Pivotal Trial by Raje et al. Published on Lancet Oncology - Vittorio Fusco; Giuseppina Campisi; Paul de Boissieu; Federico Monaco; Anna Baraldi; Gianmauro Numico; Alberto Bedogni (MDPI AG, 2018)
The recent randomized trial, published by Raje et al., on Lancet Oncology is potentially practice changing. It proposes that denosumab is a valid alternative to zoledronic acid in the treatment of myeloma patients. However, several points need further data and more details, such as information on incidence, diagnosis, and follow-up of osteonecrosis of the jaw (ONJ) cases, observed among treated patients. Adopted definition to adjudicate ONJ cases, type of registration of potential ONJ cases, length of observation are possible causes of potential underestimation of ONJ incidence in their study. Future updated evaluations with longer follow-up, and including actuarial estimation, are required for final judgment on ONJ risk in myeloma patients receiving denosumab, and comparison with ONJ risk by zoledronic acid.